2001
DOI: 10.1116/1.1349723
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and aging of organosiloxane and fluorocarbon films grown from hyperthermal polyatomic ions

Abstract: Polyatomic ions can be used to deposit thin films, modify the phases of interfaces, dope trace elements into interface regions, impact specific chemical functionalities to a surface, and create micron- and nanometer-scale interface structures. This article demonstrates the broad flexibility over the modified surface properties allowed by variation of the incident ion chemical structure and kinetic energy. Organosiloxane (OS) films are deposited here on Al from mass-selected 15–100 eV Si2O(CH3)5+ ions. Monochro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…The role of ions in film formation is the subject of considerable debate. Studies using polyatomic hyperthermal ions show that polymer film growth is possible, albeit slow 12, 13. However, these studies use beams of a mass‐selected ion and these ions are much smaller than those detected in the plasma‐MS of VOCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of ions in film formation is the subject of considerable debate. Studies using polyatomic hyperthermal ions show that polymer film growth is possible, albeit slow 12, 13. However, these studies use beams of a mass‐selected ion and these ions are much smaller than those detected in the plasma‐MS of VOCs.…”
Section: Resultsmentioning
confidence: 99%
“…This view is partially supported by ion beam studies: for example, the group of Hanley has demonstrated that polymeric coatings can be grown from beams of polyatomic hyperthermal ions using total ion fluences in the range of 2.5 × 10 15 –6 × 10 16 ions · cm −2 12, 13. In reference12 Hanley et al have grown thin film polymer coatings from beams of the polyatomic hyperthermal m / z 147 ion, derived from hexamethyldisiloxane (HMDSO), using total ion fluences and energies that we believe approximate to those in HMDSO plasma. By X‐ray photoelectron spectroscopy (XPS) and secondary ion mass spectrometry (SIMS) it was shown that there was very close agreement in the chemistry and molecular structure of these ion‐beam derived coatings to those deposited from plasmas of HMDSO.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…While the energy per monomer molecule in the plasma phase is pressure-invariant, the higher pressure enhances the residence time close to the surface and affects ion-assisted processes (due to more collisions). Additional effects related to the ion energy delivered to the surface are discussed in the literature including the contribution of hyperthermal intact molecular ions which becomes important at enhanced pressures [33,34]. Such ions (as formed in the gas phase at moderate energy input) arrive at low energies (several eV) at the surface resulting in their "soft landing".…”
Section: Deposition Rate Of C:h:o Films At Various Conditionsmentioning
confidence: 99%
“…[21][22][23][24] Tra-ditionally, neutral chemistry was thought to dominate plasma polymer surface reactions, as in other plasma-enhanced chemical vapor deposition processes. This regards the relative importance of ions versus neutrals to the gas-surface dynamics.…”
Section: Introductionmentioning
confidence: 99%